Mexican American and immigrant poverty in the United State - Garcia, Ginny (Dordrecht : Springer, 2011)
Mexican-Americans and Mexican immigrants to America experience high rates of poverty that persist despite their relative family stability. This book's empirical analysis of the issues includes historical context as well as discussion of undocumented migrants.
Includes bibliographical references (p. 197-201) and index.
Keywords: Mexican Americans -- Southwestern States -- Economic conditions; Mexican Americans -- Southwestern States -- Social conditions; Mexicans -- Southwestern States -- Economic conditions; Mexicans -- Southwestern States -- Social conditions; United States -- Emigration and immigration -- Economic aspects; United States -- Emigration and immigration -- Social aspects